Challenges in stafng of TB services with phthisiologists - I. A. Vasilyeva; S. A. Sterlikov; L. E. Parolina; V. V. Testov; A. V. Gordina; N. P. Doktorova (Туберкулез и болезни лёгких)
In order to understand problems, resources, and ways of improving TB epidemic situation, it is important to analyze stafng of TB Services.Subjects and Methods. The number of phthisiologists, full-time and employed positions of phthisiologists in 2011-2020 was assessed based of Federal Statistical Surveillance Form no. 30, and for the period of 2005-2014, Form no. 17 was additionally used. The number of phthisiologists was calculated as the ratio of the number of phthisiologists (Form no. 30) to the population at the end of the reporting year multiplied by 10,000. The physician workforce capacity was additionally analyzed based on audit reports of on-site visits in 10 regions of the Russian Federation (RF) in 2021.Results. As of late 2020, the stafng level with physical persons amounted to 52.5%, the shortage of personnel was more than 4,000 phthisiologists. The provision of the population with phthisiologists ranged from 0.49 (2014) to 0.47 per 10,000 population (2020). In 2011-2020, the coefcient of part-time employment varied from 1.6 to 1.7, exceeding the regulatory value (no more than 1.5) but for 2019. The sampling analysis in 10 regions of the Russian Federation demonstrated that the proportion of phthisiologists of retirement age among physicians was 37.2%. In 2011-2020, the number of tuberculosis patients per one phthisiologist position  decreased from 19.0 to 7.8, the number of patients with multiple drug resistant tuberculosis - from 2.7 to 2.1. There is a significant decrease in the number of staﬀ positions and occupied positions of phthisiologists providing medical care in out-patient settings (by 14.0%), while the number of phthisiologists in in-patient facilities remained the same.Conclusion. Challenges in stafng of TB Services are as follows: shortage of personnel, high level of phthisiologists working part-time, insufcient stafng of out-patient and polyclinic services, high proportion of physicians of pre-retirement and retirement age and insufcient level of professional competence of young specialists.